THE ILLEGAL FINANCIAL TURNOVER IN POLAND IN THE OPINION OF WORKERS OF BANKING SECTOR - Deluga, Włodzimierz (Acta Scientiarum Polonorum. Oeconomia, 2002)
The article illustrates the attitude of banking system personnel to the illegal turnover of money coming from unknown sources. The analysis of data obtained from the research as well as presented assessments show distinctly the necessity to make constantly observations and to submit suggestions and regulations rebating to the fight against this problem, particularly in relation to the influence that it has on the economies of the countries entangled in that trade.